2017
DOI: 10.1186/s13102-017-0085-x
|View full text |Cite
|
Sign up to set email alerts
|

Limb symmetry during double-leg squats and single-leg squats on land and in water in adults with long-standing unilateral anterior knee pain; a cross sectional study

Abstract: BackgroundThe presence of pain during movement typically results in changes in technique. However, the physical properties of water, such as flotation, means that water-based exercise may not only reduce compensatory movement patterns but also allow pain sufferers to complete exercises that they are unable to perform on land. The purpose of this study was to assess bilateral kinematics during double-leg squats and single-leg squats on land and in water in individuals with unilateral anterior knee pain. A secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 34 publications
(85 reference statements)
2
25
0
Order By: Relevance
“…Moreover, the authors provided information about the three kinds of usage that each sensor has: (i) accelerometer (range: ±2 g, ±6 g; bandwidth: 50 Hz; resolution: 14 bit; noise: 128 ug/ . Two other studies used five sensors (tri-axial accelerometer and gyroscope) with an acquisition frequency of 100 Hz [15,16]. None of the four selected studies report any kind of information about the sensors' sealing.…”
Section: Sensor Specificationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, the authors provided information about the three kinds of usage that each sensor has: (i) accelerometer (range: ±2 g, ±6 g; bandwidth: 50 Hz; resolution: 14 bit; noise: 128 ug/ . Two other studies used five sensors (tri-axial accelerometer and gyroscope) with an acquisition frequency of 100 Hz [15,16]. None of the four selected studies report any kind of information about the sensors' sealing.…”
Section: Sensor Specificationsmentioning
confidence: 99%
“…The study by Fantozzi et al [12] reported that the participants were healthy (males and females), and Severin et al [16] reported such data per sex. Other studies split the participants into healthy or with some pathology (in that study, particular cases had chronic anterior knee pain) and did not mention the participants' sex [15]. It only mentioned that both groups (young adults with chronic anterior knee pain and healthy adults) were age and sex matched.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations